Cigarette Smoking and Oxidative Stress in Patients with Coronary Artery Disease - Kamceva, Gordana; Arsova-Sarafinovska, Zorica; Ruskovska, Tatjana; Zdravkovska, Milka; Kamceva-Panova, Lidija; Stikova, Elisaveta (Scientific Foundation SPIROSKI, 2016)
To determine whether cigarette smoking, as a risk factor for CAD, affects (anti)oxidant status.